Evaluation of initiative by UiTM as a sustainable campus: energy / Nur Farahin Azhar - Azhar, Nur Farahin (2013)
Energy has always been an essential element for the generation of social and economic growth in a country. Malaysia has an abundance of renewable energy resources are not fully exploited. Recently, Malaysia is still very much dependent on fossil fuels as its primary source of energy. Due to the current upward trend of fuel prices, the Malaysian Government is forced to look into other alternative sources with the use of renewable energy. In order to reply the Government order, UiTM is one of the Malaysia University that study the initiative that can be done to practice saving energy activities in campus. The purpose of this study is to evaluate the effectiveness of saving energy initiative in UiTM campus in term of using energy efficient lighting system instead of using the incandescent light bulb. The study was conducted using semi-structure interview and questionnaire survey. Through this research, the effectiveness of energy saving can be shown in reductions in term of cost and carbon emission. The recommendations will be made to improve the effectiveness of energy saving in UiTM campus